Prognostic Impact of Prolonged Cross-Clamp Time in Coronary Artery Bypass Grafting - Ruggieri VG; Bounader K; Verhoye JP; Onorati F; Rubino AS; Gatti G; Tauriainen T; De Feo M; Reichart D; Dalén M; Svenarud P; Faggian G; et al. (Blackwell Science Asia, 2022)
BACKGROUND:
The prognostic impact of cross-clamp time (XCT) in patients undergoing isolated coronary artery bypass grafting (CABG) has not been thoroughly investigated.
MATERIAL AND METHODS:
2957 patients who underwent on-pump isolated CABG from the prospective multicentre E-CABG study were the subjects of this analysis.
RESULTS:
The mean XCT in this series was 58±25minutes Cross-clamp time was >60 minutes in 1134 patients (38.3%), >75minutes in 619 patients (20.9%) and >90minutes in 296 patients (10.0%). Multivariate analysis showed that XCT was an independent predictor of 30-day mortality (p<0.0001, OR 1.027, 95%CI 1.015-1.039) along with age (p<0.0001), female gender (p=0.001), pulmonary disease (p=0.001), poor mobility (p=0.002), urgency status (p=0.007), critical preoperative status (p=0.002) and participating centres (p=0.015). Adjusted risk of 30-day mortality was highest for XCT >75minutes (2.9% vs. 1.7%, p=0.002, OR 3.479, 95%CI 1.609-7.520). Analysis of 428 propensity score matched pairs showed that XCT >75minutes was associated with significantly increased risk of early mortality, prolonged use of inotropes, postoperative use of intra-aortic balloon pump, use of extracorporeal membrane oxygenation, atrial fibrillation, prolonged stay in the intensive care unit and of composite major adverse events.
CONCLUSIONS:
Isolated CABG is currently performed with prolonged XCT in a significant number of patients and this seems to be a determinant of poor early outcome.